Optimisation in the Logistics and Management of Supply Chains in Production by Textile Enterprises - Xinfeng Yan; Shakhrukh Madjidov; Habiba Halepoto; Lihong Chen (Tekstilec, 2021)
This article is devoted to questions regarding the analysis of the implementation of logistics and supply chain management conditions in textile production. Based on delivery optimisation, the authors offer a model of multimodal transportation of textile products produced in Uzbekistan. The importance of optimising the supply chain of the logistics business processes in order to decrease costs is demonstrated in this article. A mathematical model of optimisation for placement textile enterprises to stimulate the reduction of supply chain costs is recommended. However, this research would be beneficial for the textile and fashion industries. The approach might be further extended to other similar industries.